Portal inflammation during NAFLD is frequent and associated with the early phases of putative hepatic progenitor cell activation. Issue 11 (29th June 2015) - Carotti, Simone; Vespasiani-Gentilucci, Umberto; Perrone, Giuseppe; Picardi, Antonio; Morini, Sergio
Abstract : Aims: We investigated whether portal tract inflammation observed in non-alcoholic fatty liver disease (NAFLD) is associated with hepatic progenitor cell compartment activation, as thoroughly evaluated with different markers of the staminal lineage. Methods: Fifty-two patients with NAFLD were studied. NAFLD activity score, fibrosis and portal inflammation were histologically evaluated. Putative hepatic progenitor cells, intermediate hepatobiliary cells and bile ductules/interlobular bile ducts were evaluated by immunohistochemistry for cytokeratin (CK)-7, CK-19 and epithelial cell adhesion molecule (EpCAM), and a hepatic progenitor cell compartment score was derived. Hepatic stellate cell and myofibroblast activity was determined by immunohistochemistry for α-smooth muscle actin. Results: Portal inflammation was absent in a minority of patients, mild in 40% of cases and more than mild in about half of patients, showing a strong correlation with fibrosis (r=0.76, p<0.001). Portal inflammation correlated with CK-7-counted putative hepatic progenitor cells (r=0.48, p<0.001), intermediate hepatobiliary cells (r=0.6, p<0.001) and bile ductules/interlobular bile ducts (r=0.6, p<0.001), and with the activity of myofibroblasts (r=0.5, p<0.001). Correlations were confirmed when elements were counted by immunostaining for CK-19 and EpCAM. Lobular inflammation, ballooning, myofibroblast activity and hepatic progenitor cell compartment activation were associated with portal inflammation by univariate analysis. In the multivariate model, the only variable independently associated with portal inflammation was hepatic progenitor cell compartment activation (OR 3.7, 95% CI 1.1 to 12.6). Conclusions: Portal inflammation is frequent during NAFLD and strongly associated with activation of putative hepatic progenitor cells since the first steps of their differentiation, portal myofibroblast activity and fibrosis.